"A Fly in the Ointment": African American Male Preservice Teachers' Experiences With Stereotype Threat in Teacher Education. (September 2015) - Scott, Sonya V.; Rodriguez, Louie F.
This study draws from a larger phenomenological study on African American academic persistence and career aspirations in education. This article highlights three African American males' experiences with concentrated forms of stereotype threat in teacher education. Their voices revealed dimensions of how power and privilege operate in teacher education. Three themes emerged as significant factors, stereotype threat, grappling with marginalization, and significant role models, in their schooling experiences and motivations to teach. Findings of this study suggest practical implications for teacher-credential programs, faculty practice, and prospective African American male teachers.